2015
DOI: 10.1039/c5ta03989d
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of oxide ion dynamics in type-II Bi3NbO7

Abstract: Oxide ion dynamics in the type-II phase of Bi 3 NbO 7 have been studied using a series of DFT molecular dynamics calculations. Coordination numbers and angular distribution functions for both bismuth and niobium cations were analysed. A strong preference for octahedral coordination of niobium cations was observed. This has the effect of reducing the overall number of mobile vacancies in the system. Energy landscapes for the system revealed low-energy barriers for oxide ion jumps in the h100i direction. Whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Neutron powder diffraction data were collected on the Polaris diffractometer at the ISIS Facility, Rutherford Appleton Laboratory, on back-scattering (130-160 ), 90 (85-95 ), low-angle (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and very low angle (13)(14)(15) detectors over the respective time of ight ranges 1.0 to 20 ms, 0.8 to 19.2 ms, 0.5 to 20 ms and 2.0 to 18.6 ms. Room temperature data were collected with the sample contained in a cylindrical 7 mm diameter thin walled vanadium can, located in front of the back-scattering detectors, while for elevated temperatures, samples were sealed in a silica tube placed inside an 11 mm diameter thin walled vanadium can. Data were collected at 50 C intervals from 300 C to 700 C. Long data collections of 1000 mA h were made at room temperature, 500 C and 700 C to allow for total scattering analysis.…”
Section: Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron powder diffraction data were collected on the Polaris diffractometer at the ISIS Facility, Rutherford Appleton Laboratory, on back-scattering (130-160 ), 90 (85-95 ), low-angle (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and very low angle (13)(14)(15) detectors over the respective time of ight ranges 1.0 to 20 ms, 0.8 to 19.2 ms, 0.5 to 20 ms and 2.0 to 18.6 ms. Room temperature data were collected with the sample contained in a cylindrical 7 mm diameter thin walled vanadium can, located in front of the back-scattering detectors, while for elevated temperatures, samples were sealed in a silica tube placed inside an 11 mm diameter thin walled vanadium can. Data were collected at 50 C intervals from 300 C to 700 C. Long data collections of 1000 mA h were made at room temperature, 500 C and 700 C to allow for total scattering analysis.…”
Section: Diffractionmentioning
confidence: 99%
“…To avoid the inuence of thermal equilibration on the derived results, the rst 10 ps of the MD simulations were ignored. The time step used was based on the results of our previous studies on related systems, 35,42,43 which showed 10 fs to give equivalent accuracy in calculations compared to shorter time steps, when used with a suitable cut-off energy. Pair distributions, contact distances, coordination numbers and ionic density proles were calculated from the MD simulations by summation over all time steps and all ve different initial random distributions of yttrium/lead cations and oxygen vacancies at each studied temperature.…”
Section: Dft Simulationsmentioning
confidence: 99%
“…Further studies using ab initio molecular dynamics simulations have shown that Y 3+ acts as a defect trap in δ-Bi 3 YO 6 [21,22]. While supervalent dopants such as Nb 5+ also act as traps for oxide ions, they maintain high oxide ion dynamics, but the motion is mainly restricted to the coordination sphere of the dopant cation [23]. Indeed, for supervalent dopants, such as Nb 5+ , Ta 5+ and W 6+ the preferred coordination geometry of the dopant cation is particularly important and can lead to ordering phenomena [24].…”
Section: Introductionmentioning
confidence: 99%